Literature of Review The Influence of Motivation, Compensation, and Organizational Culture on Job Satisfaction among Gen Z Police Members at the East Jakarta Metro Police - Nabila Zahra Octaviany (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research is a literature review that examines theinfluence of Motivation, Compensation, andOrganizational Culture on Job Satisfaction. Thisresearch was conducted on generation Z who aremembers of the Police at the East Jakarta MetroPolice. This research uses a quantitative approachwith a population that is not known with certainty sothat the minimum sample used refers to theapproach of Hair et al.